The efficacy and safety of induction chemotherapy combined with sintilimab followed by concurrent chemoradiotherapy plus sintilimab sequencing maintaining with sintilimab for patients with unresectable locally advanced esophageal squamous cell carcinoma - Ruifeng Wang; Tianhui Guo; Qi Wang; Wen Gao; Yimiao Yu; Jun Zhang; Wenqian Fu; Haiji Wang; Biyuan Zhang (BMC Cancer)
Abstract Purpose To evaluate the efficacy and safety of induction chemotherapy combined with programmed death protein 1 (PD-1) inhibitor (sintilimab) followed by concurrent chemoradiotherapy (CCRT) plus sintilimab, and subsequent maintenance with sintilimab (IC-ICCRT-IO) for patients with unresectable locally advanced esophageal squamous cell carcinoma (ESCC) in a retrospective study. Methods Data from patients with histologically confirmed, locally advanced, inoperable ESCC who received IC-ICCRT-IO were retrospectively analyzed. Treatment effects were evaluated after 2 cycles of induction therapy and after CCRT by contrast-enhanced CT scans and esophagograms, followed by subsequent evaluations every 3 months post-treatment. The primary endpoints included progression-free survival (PFS) and PFS rates at 6, 12, and 18 months. Secondary endpoints involved overall response rate (ORR), disease control rate (DCR), overall survival (OS), and safety. The influence of the expression level of programmed death ligand-1 (PD-L1) as well as neutrophil-to-lymphocyte ratio (NLR) on efficacy of the IC-ICCRT-IO was analyzed. Results In total, 29 eligible patients were enrolled and analyzed. The median follow-up time was 20.5 months. The median PFS was not reached; the 6-, 12-, and 18-month PFS rates were 100.0%, 93.1%, and 82.8%, respectively. The median OS was not reached, and the 6-, 12-, and 18-month OS rates were all 100.0%. The ORR and DCR were 89.7% and 100.0%. Adverse events (AEs) were manageable, with grade 3 or higher AEs observed in 48.2% of patients, primarily nonimmune-related and clinically manageable. Hematologic toxicity was predominant. Two patients developed grade 3 immune-related rash, and two patients developed grade 3 radiation pneumonitis, all of whom were managed with appropriate symptomatic treatment. No significant differences in survival outcomes were observed with respect to PD-L1 and NLR. Conclusion Our results indicated that the IC-ICCRT-IO regimen for unresectable locally advanced ESCC provided a survival benefit with manageable safety profile. More prospective clinical studies should be warranted. Trial registration 2024-04-22, No. QYFY WZLL 28,684, retrospectively registered.